2018
DOI: 10.1016/j.egja.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled fascia iliaca compartment block versus fentanyl patient-controlled intravenous analgesia in patients undergoing femur fracture surgery

Abstract: Background and objectives: Postoperative pain relief is crucial in elderly, however, the use of opioids is limited owing to their potential side effects. We studied the effects of patient-controlled ultrasound guided fascia iliaca compartment block (FICB) with Levobupivacaine versus patient-controlled intravenous fentanyl on postoperative pain score in patients scheduled for fixation of femur fractures under general anesthesia. Methods: 60 patients ASA physical status I and II undergoing elective fixation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…McGraw-Tatum et al [24] identified that FICB required less overall total opioids than the control group. And FICB is a relatively safe anesthesia technique as the needle point is away from the femoral nerve, femoral artery, and femoral vein [25].…”
Section: Discussionmentioning
confidence: 99%
“…McGraw-Tatum et al [24] identified that FICB required less overall total opioids than the control group. And FICB is a relatively safe anesthesia technique as the needle point is away from the femoral nerve, femoral artery, and femoral vein [25].…”
Section: Discussionmentioning
confidence: 99%
“…A 2016 prospective RCT [ 42 ] evaluated the efficacy of FICB after hemiarthroplasty, and outcomes revealed a significant opioid-sparing effect in the first 24 h after surgery with FICB supplement. Later in 2018, an RCT [ 43 ] compared the effect of patient-controlled FICB with patient-controlled intravenous fentanyl (PC-IVF) for pain management after surgery. Outcomes showed satisfactory efficacy following FICB with decreased additional analgesia use and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Different local anaesthetic agents were compared in different concentrations [55,56] Two RCTs were done on hip surgery [57,62] and two were on generalized lower limb procedures [58,60]. Lumbar plexus block, lumbar epidural, fascia iliaca compartment block and intravenous narcotics were compared.…”
Section: Methodsmentioning
confidence: 99%